Narrative construction of leader identity in a leader development program context - Gitte P. Jakobsen (Copenhagen Business School (CBS), 2009)
With the increasing globalization, new organizational structures, and rapid change the leader has been increasingly individualized and personalized. The leader has been put under pressure to reveal a leadership, in which the personality of the individual leader is increasingly important. Moreover, the individual leader has become central for creating and communicating organizational meaning, and the leaders' personal conduct, ethics and identity are taken to be symbolic of the organizational brand. Leaders are increasingly publicly evaluated based on how he “tells the story” of him-self and the organization e.g. the extent to which the leader exemplifies and lives the organizational brand. This is reflected in a growing demand for leader development programs with a personal orientation, and psychological oriented development focused on the individual leaders' personal challenges. Recent theoretical developments in the intersection of critical management studies and narrative identity studies have challenged prior assumptions and approaches, with a departure in social constructivist perspectives leadership is conceived as narrative identity construction embedded in social practice and context. Hence, leader studies turn to investigate the emergence of leaders as processes of identity work in particular contexts, privileging the use of language, social interaction and critical reflexive approaches. This dissertation explores the narrative construction of leader identity in the context of a leader development program, examining the processes and the content of identity work of leaders. Empirically five Danish executives from five different industries have been studied in a three year period, starting with a one-year long leader development program and in two following interviews. The material is analyzed within a theoretical and methodological framework inspired by a combination of social constructivist, discursive, narrative and critical management approaches to identity and leadership research. The narrative analytical framework is based on narrative theory, narrative therapy theorization, and positioning theory, analyzing the thematic, temporal and relational aspects of the five leaders' narrative accounts. Hence, the analytical strategy analyzes the narrative recourses of: problem stories, preferred stories, storylines, and the negotiation of subject positions used by the five leaders in constructing certain situated leader identities
hdl:10398/7807
Keywords: 650